2020
DOI: 10.1093/jac/dkaa187
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of flucloxacillin dosing regimens in critically ill patients using population pharmacokinetic modelling of total and unbound concentrations

Abstract: Background Initial appropriate anti-infective therapy is associated with improved outcomes in patients with severe infections. In critically ill patients, altered pharmacokinetic (PK) behaviour is common and known to influence the achievement of PK/pharmacodynamic targets. Objectives To describe population PK and optimized dosing regimens for flucloxacillin in critically ill patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 23 publications
(29 reference statements)
2
26
1
Order By: Relevance
“…Previously, more aggressive dosing recommendations have been made based on total flucloxacillin concentrations or the oxacillin ECOFF. 10 , 20 , 22 The present data showing high target achievement with the use of the strain-specific MIC, as well as the lack of association between outcome and target achievement with the use of MSSA ECOFF, challenge current flucloxacillin dosing recommendations. In addition, dosages should only be adjusted according to the measured unbound flucloxacillin concentration in patients with MSSA-BSI, 20 as models that are able to accurately predict the unbound concentration from the total measured flucloxacillin concentration are lacking.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Previously, more aggressive dosing recommendations have been made based on total flucloxacillin concentrations or the oxacillin ECOFF. 10 , 20 , 22 The present data showing high target achievement with the use of the strain-specific MIC, as well as the lack of association between outcome and target achievement with the use of MSSA ECOFF, challenge current flucloxacillin dosing recommendations. In addition, dosages should only be adjusted according to the measured unbound flucloxacillin concentration in patients with MSSA-BSI, 20 as models that are able to accurately predict the unbound concentration from the total measured flucloxacillin concentration are lacking.…”
Section: Discussionmentioning
confidence: 68%
“…Using this approach, we observed that 90% of all patients and 100% of critically ill patients attained the optimal target (100% fT >MIC ), whereas, with 100% fT >ECOFF, only 38% of critically ill patients attained the target. In pharmacokinetic/pharmacodynamic studies, the ECOFF 20 or the EUCAST clinical species-specific breakpoint value 14 for the targeted bacterium is applied to define the target concentration of the antibacterial drug. In our study, measured flucloxacillin MICs ranged from <0.06 to 0.25 mg/L with a median value of 0.125 mg/L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum albumin was the only plasma protein taken into account as ceftriaxone is known to bind predominantly to albumin [ 27 ]. Protein binding PK parameters were, in case of linear protein binding, the linear protein binding constant and in case of nonlinear protein binding, the maximum binding capacity (Bmax), the Hill coefficient (h) and the dissociation constant (B50) ( File S2, Supplementary Materials ) [ 35 ]. Between-patient variability (BPV) was estimated for the protein binding kinetics parameters.…”
Section: Methodsmentioning
confidence: 99%
“…Hypoalbuminemia is a risk factor for treatment failure with cefotiam in bacteremia caused by gram-negative bacteria [ 194 ]. It has also been recommended that because of the high prevalence of hypoalbuminemia in critically ill patients, dose adjustments of flucloxacillin should be based on monitoring unbound concentrations to account for non-linear protein binding [ 195 ].…”
Section: Hypoalbuminemia and Antimicrobial Treatmentmentioning
confidence: 99%